I learned a lot about my classmates …’. Exploring focus group discussions as learning environment to raise controversial issues in geography and economic education. - Christiane Hintermann; Heidrun Edlinger; Matthias Fasching; Thomas Jekel (European Journal of Geography)
Teachers of geography and economics address numerous topics in the classroom which are controversially discussed in society and/or affect pupils directly. How they deal with issues such as migration or identity depends not only on the respective curriculum but also on their disciplinary knowledge and pedagogic skills. This paper argues for the need to adapt learning environments depending on educational objectives, content, age and discusses focus groups as one possible way to work with students in secondary education on sensitive matters. Focus groups are seen as a tool to enable real-world complexity in the classroom, and to prepare students for participatory, active citizenship. The paper first discusses current theoretical thought regarding controversy in both society and the classroom. It then goes on to illustrate real-world classroom experiences of focus-group based learning on controversial issues and to discuss its benefits and challenges.